2020
DOI: 10.1155/2020/9480537
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gradient Nanostructured Ti on Behaviours of MG63 Cells In Vitro

Abstract: Titanium (Ti) is widely used in oral implants. However, there is still a challenge to promote the osseointegration of bone tissue on the surface of Ti. To solve this problem, we prepared novel gradient nanostructured (GNS) Ti and studied the effect of GNS on the adhesion, proliferation, and apoptosis of MG63 cells in vitro. The results demonstrated that the GNS Ti promoted the adhesion effect and proliferation of MG63 cells better than the annealed Ti, while the ability of GNS Ti to inhibit cell apoptosis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…It is reported that the roughness of biomaterial surface plays a critical role in material biocompatibility (33). In the current research and our previous studies (34), to exclude the impact of surface roughness in material biocompatibility, the control group (CG Ti) is fabricated by SMAT treatment followed by recrystallization annealing treatment making sure a similar roughness between GNS Ti and CG Ti.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It is reported that the roughness of biomaterial surface plays a critical role in material biocompatibility (33). In the current research and our previous studies (34), to exclude the impact of surface roughness in material biocompatibility, the control group (CG Ti) is fabricated by SMAT treatment followed by recrystallization annealing treatment making sure a similar roughness between GNS Ti and CG Ti.…”
Section: Discussionmentioning
confidence: 89%
“…We found that the contact angle of GNS Ti is 53.7°±2.4°, while the contact angle of CG Ti is 96.9°±3.8°. There is a significant difference between the two groups in contact angle indicating that GNS Ti has high hydrophilicity (34). Therefore, the higher hydrophilicity of GNS Ti is a promoting factor for its higher biocompatibility.…”
Section: Discussionmentioning
confidence: 97%
“…5(d)), which is reported to be capable of keeping adsorbed proteins on its surface in a more desirable conformation. 9 Previously, Luo et al 10 conrmed that the nanostructured titanium with a more hydrophilic surface increases the amount of adsorbed protein, thus promoting the adhesion of MG63 cells. Huo et al 20 reported that SFT-derived nanograined Ti6Al4V with a more hydrophilic surface promoted the adsorption of RGD (arginine-glycine-aspartic acid)-containing anchoring proteins in a more active conformation, thereby improving osteoblastic adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that modulating surface properties, including roughness, 6,7 topography, 8 grain structure, 9,10 and chemistry, [11][12][13] is a very effective measure to improve the osseointegration of an implant as the surface characteristics of biomaterials play an important role in determining the early cellular behavior at the implant/tissue interface during the healing process. 14 Hence, surface modication provides a potential avenue to enhance the biological performance, simultaneously preserving the outstanding bulk properties of titanium-based implants.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of our research group have shown that the surface of the metal material treated by SMAT has better hydrophilicity, manifested as a smaller contact angle, and the amount of protein adsorbed on the surface and the ratio of calcium to phosphorus deposition were also significantly improved after SMAT treatment. 12,14 The surface of SMAT Ti has a larger roughness, which may be conducive to the proliferation, adhesion and osteogenic differentiation of cells within a certain range. 12,14,[51][52][53] Ludovica Parisi et al also confirmed the same point.…”
Section: Discussionmentioning
confidence: 99%